2015
DOI: 10.1002/2015jc011095
|View full text |Cite
|
Sign up to set email alerts
|

A new application of conditional nonlinear optimal perturbation approach to boundary condition uncertainty

Abstract: The conditional nonlinear optimal perturbation (CNOP) approach was mainly used to investigate the effects of the uncertainties in initial condition and model parameters on model results. This study presents a new application of the CNOP approach to the investigation of the effects of boundary condition uncertainty. Specifically, we first give the general formulation of the CNOP approach for uncertainties of initial and boundary conditions and model parameters. The method is then applied to analyze the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
0
16
0
1
Order By: Relevance
“…To distinguish with CNOP-I, we call such an optimal parameter perturbation in the constraint as CNOP-P. The CNOP method has been also extended to investigate the effects of boundary condition uncertainty (CNOP-B, Wang and Mu 2015).…”
Section: Conditional Nonlinear Optimal Perturbationmentioning
confidence: 99%
“…To distinguish with CNOP-I, we call such an optimal parameter perturbation in the constraint as CNOP-P. The CNOP method has been also extended to investigate the effects of boundary condition uncertainty (CNOP-B, Wang and Mu 2015).…”
Section: Conditional Nonlinear Optimal Perturbationmentioning
confidence: 99%
“…Many methods have been proposed to solve this problem, and conditional nonlinear optimal perturbation (CNOP) is one that fully considers nonlinear processes. The CNOP approach was originally proposed to solve the uncertainty in the initial condition (Mu et al, 2003), and further extended to the uncertainties in the model parameters (Mu et al, 2010), model tendency (Duan and Zhou, 2013) and boundary condition (Wang and Mu, 2015). The CNOP approach is well summarized by Wang et al (2019), and so we just briefly introduce the application of CNOP in estimating the initial and boundary condition uncertainties.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to initial perturbations, optimal boundary per-turbations have been investigated in an ocean ecosystem model (Wang and Mu, 2015). The results revealed that nonlinear processes play important roles in the phytoplankton evolution caused by nutrient perturbations at the bottom boundary.…”
Section: Applications Of the Cnop Approach In Related Investigationsmentioning
confidence: 99%
“…2003 年, CNOP 方法首次被提出时主要是探讨初始条件误差对大气 -海洋预报的影响 (参见文 献 [12]), 此后, 该方法被逐步发展完善. 2010 年, 此方法被扩展到评估模式参数误差的影响 (参见文 献 [21]), 最近其又被进一步扩展到研究模式倾向误差 [22] 和边界条件误差 [23] 的影响. 本节将这些工作 统一到一个框架下来阐述 CNOP 方法.…”
Section: 拓展的条件非线性最优扰动方法unclassified